Characteristics of Organic Matter Pores and the Relationship with Current Pressure System of Lower Silurian Longmaxi Shales in Dingshan Field, Southern Sichuan, China. (8th October 2021) - Cao, Qian; Jiang, Ke; Wen, Zhentao; Wang, Xingzhi; Qi, Minghui; Yin, Zhongshan
Abstract : Organic matter pores (OMP) provide significant storage space for hydrocarbons in lower Silurian Longmaxi shales in the Dingshan field of southern Sichuan, China. The distributions of organic matter and the different OMP structure parameters were characterized through Ar-ion polishing, scanning electron microscopy (SEM), and image analysis software for shale samples of different wells. The research results indicated that organic matter has been divided into two categories based on its occurrence, location, and its relationship with authigenic minerals: organic matter in situ and migrated organic matter. OMP for organic matter in situ are mainly micropores mostly arranged isolatedly, while in migrated organic matter pores show larger sizes and higher roundness. The development of OMP in samples is predominantly controlled by the formation pressure. The existence of overpressure alleviated the stress on the rock skeleton, causing the compaction of some migrated organic matters to lag or decrease. This played a positive role in protecting the development of pores in the interior and edge of the rock skeleton, and it can also induce the development of microfractures in shale. The protective effect of formation pressure on organic pores was provided for understanding the exploration and exploitation of Longmaxi shales in the study area.